Implementasi dan Kendala Penilaian Sasaran Kinerja Pegawai pada Kementerian Luar Negeri - Pritta Dhiya Prameswari; Veithzal Rivai Zainal; Lenny Christina Nawangsari (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Performance appraisal of Civil Servants (PNS) has a very important role in seeing the extent to which civil servants provide performance to the organization, determining the development of competencies and career paths. Performance appraisal regulations that have evolved from time to time are a challenge to be implemented in government agencies. In the period before 2021 back, government agencies carried out performance assessments with Employee Performance Targets (SKP) using Government Regulation Number 46 of 2011. Not apart from the Ministry of Foreign Affairs, the SKP performance appraisal management system was web-based. Regulations changed and refined with Government Regulation Number 30 of 2019 concerning the Assessment of Civil Servants' Work Performance. Significant differences are obtained from the value and period of assessment. This makes it necessary to update the web-based management system for the implementation of performance appraisals with new regulations. The readiness of human resources in civil servants especially for Ministry of Foreign Affairs also to implement PP 30/2019 needs to be equipped with socialization and technical guidance that is well planned and directed to be right on target so that the performance appraisal of civil servants can better document the outcomes recorded in the PNS SKP in a certain assessment period.